Primary Adenosquamous Cell Carcinoma of the Pancreas: A Case Report with a Review of the Korean Literature - Na, Youn Ju (The Korean Association of Internal Medicine, 2011)
The most common pancreatic cancer is adenocarcinoma. Primary adenosquamous cell carcinoma of the pancreas is very rare and aggressive. A 46-year-old man presented with a 3-month history of dyspepsia and a 7-kg weight loss. The physical examination showed tenderness of the right upper quadrant of the abdomen. There was no jaundice. Amylase and lipase were elevated. CA 19-9 was elevated to 566.7 U/mL. Gastroduodenoscopy showed a hard ulceroinfiltrative mass with a yellowish exudate that bled readily on touch in the second portion of the duodenum. Abdominal computed tomography showed a 7.1 × 6.3-cm heterogeneously enhancing mass in the pancreatic head. The pancreatic mass had invaded the duodenum wall, gastric antrum, and gastroduodenal artery sheath. Fine-needle aspiration biopsy of the pancreatic mass revealed adenosquamous cell carcinoma, anaplastic type. We concluded that an adenosquamous cell carcinoma of pancreas had invaded the duodenal mucosa causing ulceration.